Robinson v. Chief Constable of West Yorkshire Police - Goudkamp, J; Nolan, D (De Gruyter, 2023)
In the United Kingdom, as in some other parts of the Commonwealth, the courts have long embarked on a search for a general formula which can be applied to determine whether a duty of care arises in any given negligence case. In 2018, the United Kingdom Supreme Court delivered its judgment in Robinson v. Chief Constable of West Yorkshire Police, in which a plurality strikingly rejected as misconceived attempts to identify such a general test. Duty cases, the Supreme Court held, are to be decided by reference to precedent where applicable, or (where no such precedent applies) by analogy with the existing authorities. This approach curtails the role of policy in the duty of care enquiry. In this article, the decision in Robinson is put in context and its significance explained. It is argued that the approach to the duty question adopted in Robinson should be welcomed. Not only is that approach the best of the alternatives available, but it is the only one that is consistent with the methodology of the common law and the rule of law.